A DATA-DRIVEN FRAMEWORK FOR ASSESSING GOVERNMENT READINESS FOR PRIVATE BLOCKCHAIN ADOPTION - Shunmugam, Sivamohan V.; Kiah, Miss Laiha Mat; Azzuhri, Saaidal Razalli; Lau, Sian Lun (Malaysian Journal of Computer Science, 2024)
The transformative potential of private, permissioned blockchains for public service delivery is widely recognized, offering significant improvements in data integrity, transparency, and process efficiency through decentralized and unchangeable ledgers. Despite this appeal, a notable gap exists in the literature regarding a structured, data-driven framework to systematically assess government readiness for blockchain adoption. The absence of such a diagnostic tool often leads to ad-hoc, trial-and-error implementations that frequently fail to scale or integrate effectively with existing systems. This study addresses this gap by proposing and empirically validating a comprehensive, multi-dimensional framework for assessing government readiness. The methodology involved the design of a conceptual model, the development of a functional prototype, and its subsequent quantitative validation through a survey of domain experts. The findings demonstrate the framework's effectiveness in providing an integrated analysis of the technical, organizational, and environmental factors crucial for successful blockchain adoption. This research contributes to theoretical knowledge by operationalizing readiness constructs and also offers a practical, evidence-based diagnostic tool for policymakers and public managers to inform investment decisions and mitigate adoption risks.